Integrative Analysis of FinTech Innovations in Industry: Enhancements and Challenges - Abedalrhman, Kahtan (International Journal of Engineering and Management Research, 2024)
This paper presents a detailed examination of the transformative role of Financial Technology (FinTech) innovations across various industry sectors, highlighting both the enhancements and the inherent challenges these technologies introduce. By integrating a range of data sources, including case studies and empirical research, the study evaluates the efficacy of FinTech applications in optimizing operational efficiency, enhancing data-driven decision-making, and fostering sustainable growth in industrial operations. While the adoption of FinTech offers significant advantages, such as improved transaction speed and accuracy, reduced costs, and enhanced security, it also poses several challenges. These include technological integration issues, regulatory compliance burdens, and the need for substantial upskilling of the workforce. The paper also explores the dynamic interplay between technological advances and regulatory frameworks that shape the adoption and impact of FinTech solutions. Through this integrative analysis, the study aims to provide stakeholders with a nuanced understanding of the benefits and obstacles associated with FinTech innovations in the industry, offering a roadmap for navigating the complexities of this rapidly evolving landscape.